Once-weekly semaglutide use in glucagon-like peptide-1 receptor agonist naïve patients with type 2 diabetes in North Macedonia: Real-world data from the MIRAGE study - Milenkovikj, Tatjana; Chekorova Mitreva, Biljana; Jovanovska Mishevska, Sasha; Bitoska-Mileva, Iskra; Ahmeti, Irfan; the MIRAGE study group; Mucha, Argjent; Mladenovska Stojkoska, Ivana (Elsevier BV, 2023)
Aims The MIRAGE study aimed to evaluate the real-world use of once weekly (OW) subcutaneous semaglutide in glucagon-like peptide-1 receptor agonist naïve type 2 diabetes patients in routine clinical practice in North Macedonia. Methods MIRAGE was a multicentre, single-arm, retrospective and 30-weeks study, conducted in North Macedonia. Primary [change in glycated haemoglobin (HbA1c)] and secondary endpoints [change in body weight, fasting plasma glucose (FPG), lipid parameters, blood pressure, waist circumference, glycaemic and weight-loss target achievement] were evaluated between baseline and end of study (EOS). Results Baseline characteristics of 314 patients enrolled in the study were, mean age: 55.5 years, HbA1c: 9.0%, diabetes duration: 7.8 years, body weight: 105.2 kg and waist circumference: 114 cm. Patients at EOS experienced statistically significant estimated mean change in HbA1c: -2.2% points, body weight: -9.0 kg, and FPG: -4.1 mmol/L (all p<0.0001). At EOS, 62.1% patients achieved HbA1c <7%, and 79.3% had ≥1% HbA1c reduction. A weight reduction of ≥3% and ≥5% was noted in 88.3% and 73.3% patients, respectively. No new safety concern has emerged. Conclusions Findings from MIRAGE study demonstrated glycaemic and weight-loss benefits of semaglutide, with improvements in other cardiometabolic parameters. The study supports real-world OW subcutaneous semaglutide use in North Macedonia.
Keywords: Fasting plasma glucose; Glucagon-like petide-1 receptor agonist; Glycated haemoglobin; Semaglutide; Subcutaneous; Type 2 diabetes